Professional self-fulfilment of skilled people of different professional groups and specialities - Kokun, Oleg M. (Social Welfare: Interdisciplinary Approach, 2015)
Objective trends of society development encourage substantially increased attention to the problem of person’s self-fulfilment. Its insufficient understanding determines the necessity of its theoretical justification as well as empirical study. The article presents the research aimed at determination of comparative features of professional self-fulfilment of skilled person working at 10 different lines of profession
Keywords: self-fulfilment; professional self-fulfilment; professional development; factors of self-fulfilment; self-fulfilment attributes